2022
DOI: 10.4236/oji.2022.121001
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Plasma Galectin-3 Concentrations, Inflammatory Cytokines Levels and Lymphocytes Status in Breast Cancer under Chemotherapy

Abstract: We investigated relationship between galectin-3 (Gal-3) levels and T lymphocytes apoptosis and the activation rates in breast cancer during chemotherapy. We used plasma samples from 112 women classified into two groups: 70 women with breast cancer (BC) and submitted to neoadjuvant chemotherapy (3 cycles) and 42 healthy women used as controls. In the group of BC, blood samples were taken before each cycle of chemotherapy and Gal-3 levels was evaluated by ELISA sandwich. Flow cytometry was used to study T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Galectin‐3 could become a biomarker in several neoplastic diseases (Table 2) 133 of which there is a limited amount of data from Africa. In our previous investigation, we demonstrated that galectin‐3 plasmatic concentrations were higher in breast cancer patients compared with healthy controls and were positively correlated with breast tumor sizes 76 . Significantly higher levels of this lectin were observed in breast tumors compared with precancerous tissues as well as the triple‐negative breast cancer molecular subtype has the greatest galectin‐3 expression 134 .…”
Section: Galectin‐3 As Biomarker In Breast Cancermentioning
confidence: 93%
See 3 more Smart Citations
“…Galectin‐3 could become a biomarker in several neoplastic diseases (Table 2) 133 of which there is a limited amount of data from Africa. In our previous investigation, we demonstrated that galectin‐3 plasmatic concentrations were higher in breast cancer patients compared with healthy controls and were positively correlated with breast tumor sizes 76 . Significantly higher levels of this lectin were observed in breast tumors compared with precancerous tissues as well as the triple‐negative breast cancer molecular subtype has the greatest galectin‐3 expression 134 .…”
Section: Galectin‐3 As Biomarker In Breast Cancermentioning
confidence: 93%
“…In our previous investigation, we demonstrated that galectin-3 plasmatic concentrations were higher in breast cancer patients compared with healthy controls and were positively correlated with breast tumor sizes. 76 Significantly higher levels of this lectin were observed in breast tumors compared with precancerous tissues as well as the triple-negative breast cancer molecular subtype has the greatest galectin-3 expression. 134 In a study of Zhang and colleagues, 12 galectin-3 was consistently expressed in triple-negative breast carcinoma associated with specific clinicopathologic and immunohistochemical features, thus making it a novel subtype-specific marker in breast cancer and a potential target for overcoming chemo-resistance.…”
Section: Galectin-3 As Biomarker In Breast Cancermentioning
confidence: 95%
See 2 more Smart Citations